1996
DOI: 10.1093/oxfordjournals.aje.a008750
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Factors for Prostate Cancer: Results from a Case-Control Study in Montreal, Quebec, Canada

Abstract: A population-based case-control study of cancer and occupation was carried out in Montréal, Canada. Between 1979 and 1986, 449 pathologically confirmed cases of prostate cancer were interviewed, as well as 1,550 cancer controls and 533 population controls. Job histories were evaluated by a team of chemist/hygienists using a checklist of 294 workplace chemicals. After preliminary evaluation, 17 occupations, 11 industries, and 27 substances were selected for multivariate logistic regression analyses to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
5
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 21 publications
8
99
5
2
Order By: Relevance
“…In a Swedish study (105), nitrate fertilizer workers had an elevated prostate cancer risk. A population-based casereferent study (106) among men in Montreal, Canada, provided evidence on the possible associations between many types of cancer, including prostate cancer, and hundreds of occupational exposures. There was moderately strong support for risk of prostate cancer due to metal dust (RR 1.2, 95% CI 0.9-1.8).…”
Section: Criteria Used For Selecting the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Swedish study (105), nitrate fertilizer workers had an elevated prostate cancer risk. A population-based casereferent study (106) among men in Montreal, Canada, provided evidence on the possible associations between many types of cancer, including prostate cancer, and hundreds of occupational exposures. There was moderately strong support for risk of prostate cancer due to metal dust (RR 1.2, 95% CI 0.9-1.8).…”
Section: Criteria Used For Selecting the Studiesmentioning
confidence: 99%
“…There was moderately strong support for risk of prostate cancer due to metal dust (RR 1.2, 95% CI 0.9-1.8). Aronsen et al (106) concluded: "While the population attributable risk, estimated at between 12% and 21% for these occupational exposures, may be an overestimate due to our method of analysis, even if the true attributable fraction were in the range of 5-10%, this represents an important public health issue [p 363]." The upper limit of the 95% CI for the attributable fraction for prostate cancer was 30%.…”
Section: Criteria Used For Selecting the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both casecontrol [12] and cohort [13] studies have found that most jobs associated with occupational PAH exposure have the potential for prostate cancer. Associations between prostate cancer and specific occupational PAH exposure sources have also been reported [14,15]. In addition, we have recently shown that PAH-DNA adducts form in the prostate, and vary in level according to cellular histology [16].…”
Section: Introductionmentioning
confidence: 79%
“…A large casecontrol study found that most of the jobs associated with prostate cancer had the potential for occupational PAH exposure [12]. In three separate studies that examined specific occupational exposures, two found modest associations between selected PAH sources and prostate cancer [14,15], while the third found no link between PAH-related exposures and prostate cancer [42]. It is important to note that the two studies that found some associations between PAH exposures and prostate cancer used the expert review method utilized in the present study, whereas the negative study only used self-reported data.…”
Section: Discussionmentioning
confidence: 99%